Therapeutic outcome of melasma treatment by dual-wavelength (511 and 578 nm) laser in patients with skin phototypes III-V - S. Eimpunth (2018)
Background Recent evidence suggests that vascular abnormalities are involved in the pathogenesis of melasma. Copper bromide (CuBr) laser, which emits dual wavelengths (511 and 578 nm), enabling simultaneous and selective destruction of melanin-containing cells and blood vessels, may be of benefit in the treatment of melasma. Aim To investigate the efficacy and adverse effects (AEs) of CuBr laser for melasma treatment in patients with skin phototypes III-V. Methods We enrolled 24 Thai women with melasma to receive six CuBr laser treatments, 2 weeks apart. Objective (colour measurement) and subjective (clinical evaluation of photographs by three dermatologists blinded to the order of the photographs) assessments were obtained at baseline, after three and six treatments, and at the 3-month follow-up visit. A visual analogue scale (VAS) was used for patient assessment of change at baseline, after six treatments and at the 3-month follow-up. AEs were recorded at every follow-up visit. Results Of the 24 patients, 20 completed the study. Mean melanin index (MI) showed no statistically significant improvement compared with baseline measurements at any of the follow-up visits. There were significant improvements in clinical evaluation after three treatments (P = 0.00); however, this difference was no longer visible after six treatments. At follow-up 1 week after the end of the full course of six treatments, there was an improvement in VAS (P = 0.02). However, there was no improvement as measured by clinical evaluation or MI. Mild, transient AEs including erythema, burning sensation, scaling, hyperpigmentation and crusting were noted. Conclusions CuBr laser did not show effectiveness in improving melasma in patients with skin phototypes III-V. © 2014 British Association of Dermatologists.